Space Weather Monitor at the L5 Point: A Case Study of a CME Observed with STEREO B. Issue 10 (1st October 2020) - Rodriguez, L.; Scolini, C.; Mierla, M.; Zhukov, A. N.; West, M. J.
Abstract: An important location for future space weather monitoring is the Lagrange point 5 (L5) of the Sun‐Earth system. We test the performance of L5 for space weather monitoring using STEREO B observations of an Earth‐directed coronal mass ejection (CME), seen as a partial halo by SOHO at L1. STEREO B (located close to L5) continuously tracked the CME. By using these data in combination with methods to calculate the CME arrival time at the Earth (extrapolation, drag‐based model, and a magnetohydrodynamic model), we demonstrate that the estimation of the CME arrival time can be drastically improved by adding L5 data. Based on the L1 data alone, one could predict that the CME would arrive at the Earth. Using only the L5 data, one would not expect an arrival, as the estimations of the CME 3‐D configuration is uncertain. The combination of L1 and L5 data leads to an ambiguous prediction of the CME arrival due to low CME brightness in L1 data. To obtain an unambiguous prediction, one needs its 3‐D configuration, from observing the CME material close to the plane of the sky from at least two viewpoints (in this case L5 and, coincidentally, L4). This event demonstrates that L1 observations may be better to determine CME arrival, but L5 observations are superior for constraining arrival time. In this work, the advantages and caveats of using data from a space weather monitor at L5 for predicting interplanetary propagation of CMEs are discussed and demonstrated in a direct case study. Key Points: The Lagrange point 5 (L5) of the Sun‐Earth system is an important location for space weather monitoring We test the performance of the L5 location for space weather monitoring using STEREO B observations of an Earth‐directed coronal mass ejection (CME) By using data from L5, an improved and continuously updated estimation of the CME arrival time can be provided